Islamic Education Funding Management at MTs Miftahul Ulum Jember - Taufik, Taufik; Zaini, Zainuddin Al Haj; Fauzi, Imron (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
the purpose of this study is to find out and analyze the management of Islamic education financing at Madrasah Tsanawiyah Miftahul Ulum Jember which is focused on 1) Funding Sources and 2) Educational Financing Planning contained in the RKAM. The research method uses a qualitative approach . Data was collected through the process of observation, interviews and documentation with the head of the madrasa and administrative staff. The results of the study revealed that MTs Miftahul Ulum is a formal institution under the Miftahul Foundation Ulum has a source of education financing income based on observations through BOSDA, BOSNAS and Voluntary Assistance (SPP) as stated in the RAPBM MTs Miftahul Ulum . MTs Miftahul financing planning Ulum is contained in the Draft Madrasah Revenue and Expenditure Budget, where the steps include: 1) Each person in charge of the 8 Competency National Education Standards that has been formed by the Madrasah Head makes budget planning according to targets and needs taking into account the scale of needs, namely short term and long term , 2) Previously the Madrasah Head had formed a team in charge of making the Madrasah Activity Plan (RKM) for the 2018 – 2022 period, 3) The Madrasah Head and the team in charge of RKM carried out matching the budget proposed by the person in charge 8 Competence of National Education Standards with the Vision and Mission of the Madrasa within a period of time In the next 4 years , 4) Approval meetings are enacted in making the RKM which involve all madrasah stakeholders. The following is the Madrasah Activity Plan and Budget at MTs Miftahul Ulum.